Vapor-deposition film, multilayer structure, molded product

A uniaxially stretched EVOH film with a metal vapor-deposited layer addresses the barrier property deficiencies of existing films, enhancing both gas impermeability and metal interaction.

JP2025008213APending Publication Date: 2025-01-20MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023110177
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing vapor-deposited multilayer films using EVOH with ethylene contents of 32 mol% exhibit insufficient gas barrier properties, necessitating improvement.

Method used

A uniaxially stretched base film containing EVOH with a single ethylene content of less than 32 mol% and a metal vapor-deposited layer, such as aluminum, is used to enhance barrier properties and interaction with metals.

Benefits of technology

The resulting film achieves excellent barrier properties and strong interaction with metals, improving heat resistance and gas impermeability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008213000001
    Figure 2025008213000001
Patent Text Reader

Abstract

To provide a vapor-deposition film that offers superior barrier properties, exhibits enhanced interaction with metal, and includes EVOH-containing layers, as well as a multilayer structure and a molded product, including the vapor-deposition film.SOLUTION: A vapor-deposition film includes: a base film with a layer containing an ethylene-vinyl alcoholic copolymer; and a metal vapor-deposition layer. The base film is an uniaxially stretched film. The ethylene-vinyl alcoholic copolymer has a single ethylene unit content, with an ethylene content of less than 32 mol%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a vapor-deposited film, a multilayer structure, and a molded article, and more specifically to a vapor-deposited film having excellent barrier properties and high resistance to interaction with metals, and a multilayer structure and a molded article containing the same.

[0002] Ethylene-vinyl alcohol copolymers (hereinafter sometimes referred to as "EVOH") have very strong intermolecular forces due to hydrogen bonds between hydroxyl groups present in the polymer side chains. As a result, they are highly crystalline, and the intermolecular forces are also strong in the amorphous parts, so films using EVOH are difficult for gas molecules to pass through and show excellent gas barrier properties. For this reason, EVOH is used as a gas barrier layer to impart gas barrier properties to multilayer structures such as films and containers in a wide range of fields such as food packaging.

[0003] For example, the Examples of Patent Document 1 disclose a vapor-deposited multilayer film in which aluminum is vapor-deposited onto a stretched film made of EVOH having an ethylene content of 32 mol % (Patent Document 1: paragraph

[0040] , etc.). In addition, the examples of Patent Document 2 disclose a vapor-deposited multilayer film in which aluminum is vapor-deposited onto a biaxially stretched film made of EVOH having an ethylene content of 32 mol % (Patent Document 2: paragraph

[0143] , Table 1, etc.). In addition, the examples of Patent Document 3 disclose a vapor-deposited multilayer film in which aluminum is vapor-deposited onto a uniaxially stretched multilayer film using two types of EVOH having different ethylene unit contents (Patent Document 3: paragraph

[0084] , etc.). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-290108 A [Patent Document 2] JP 2016-028886 A [Patent Document 3] International Publication No. 2021 / 210606 Summary of the Invention [Problem to be solved by the invention]

[0005] In Patent Document 1, a stretched film of EVOH having an ethylene content of 32 mol % is used, and therefore the barrier property tends to be insufficient, leaving room for improvement. Furthermore, in Patent Document 2, a biaxially stretched film using EVOH with an ethylene content of 32 mol % is used, and therefore the barrier property is likely to be insufficient, leaving room for improvement. Furthermore, in Patent Document 3, a uniaxially stretched film using EVOH is used, but since two types of EVOH having different ethylene unit contents are used, the barrier property is likely to be insufficient, leaving room for improvement.

[0006] The present invention has been made in view of the above problems, and provides a vapor-deposited film having a layer containing EVOH, which has excellent barrier properties, particularly oxygen barrier properties, and further has strong interaction with metals (in other words, excellent heat resistance), and a multilayer structure and a molded article containing the same. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems, and as a result have found that the barrier properties and interaction with metals can be improved by laminating a metal vapor deposition layer onto a uniaxially stretched substrate film containing EVOH having a single ethylene content and an ethylene content of less than 32 mol%.

[0008] That is, the present invention has the following aspects. [1] A vapor-deposited film comprising a base film having a layer containing an ethylene-vinyl alcohol-based copolymer, and a metal vapor-deposited layer laminated on the base film, wherein the base film is a uniaxially stretched film, and the ethylene-vinyl alcohol-based copolymer has a single ethylene unit content and an ethylene content of less than 32 mol%. [2] The vapor-deposited film according to [1], wherein the base film is a uniaxially stretched film having a stretch ratio of 3 or more. [3] The vapor-deposited film according to [1] or [2], wherein the substrate film is a multilayer film further having a layer containing a thermoplastic resin. [4] The vapor-deposited film according to any one of [1] to [3], wherein the metal vapor-deposited layer comprises at least one selected from the group consisting of aluminum, gold, silver, copper, titanium, nickel, chromium, tin, and indium. [5] A multilayer structure comprising the vapor-deposited film according to any one of [1] to [4]. [6] A molded article comprising the vapor-deposited film according to any one of [1] to [4]. Effect of the Invention

[0009] According to the present invention, a metal vapor deposition layer is laminated on a uniaxially stretched substrate film containing EVOH having a single ethylene unit content and an ethylene content of less than 32 mol%, thereby making it possible to obtain a vapor deposition film that has excellent barrier properties and strong interaction with metals (excellent heat resistance). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described below based on examples of the mode for carrying out the present invention. However, the present invention is not limited to the embodiment described below.

[0011] In the present invention, when expressed as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably larger than X" or "preferably smaller than Y". Furthermore, when it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning that "it is preferably greater than X" or "it is preferably less than Y". Furthermore, "x and / or y (x and y are optional configurations)" means at least one of x and y, and means the following three cases: x only, y only, and x and y.

[0012] In the present invention, the term "film" includes the meanings of "tape" and "sheet".

[0013] Hereinafter, the monomer units contained in EVOH and thermoplastic resins may be simply referred to as “units.” For example, a monomer unit based on ethylene may be referred to as an “ethylene unit.”

[0014] <<Deposition film>> A vapor-deposited film (hereinafter, sometimes referred to as "the present film") according to one embodiment of the present invention comprises a base film and a vapor-deposited metal layer laminated on the base film. Each component will be described below.

[0015] <Base film> The base film has a layer containing EVOH (hereinafter, referred to as "EVOH layer"). Each component of the base film will be described below.

[0016] [EVOH layer] The EVOH layer is formed from an EVOH composition containing EVOH. The EVOH can be obtained by saponifying an ethylene-vinyl ester copolymer. A representative vinyl ester is vinyl acetate, but other fatty acid vinyl esters (vinyl propionate, vinyl pivalate, etc.) can also be used. The ethylene-vinyl ester copolymer can be produced by any known polymerization method, such as solution polymerization, suspension polymerization, emulsion polymerization, etc., and the saponification of the ethylene-vinyl ester copolymer can also be carried out by a known method.

[0017] The ethylene unit content of the EVOH is less than 32 mol%, preferably 22 to 30 mol%, and particularly preferably 25 to 30 mol%, as measured based on ISO 14663. When the ethylene unit content of the EVOH is within the above range, the interaction with the metal vapor deposition layer is excellent, and the transparency of the present film tends to be improved.

[0018] In addition, the EVOH used in the present film has a single ethylene unit content. That is, the EVOH layer does not contain two or more types of EVOH with different ethylene unit contents. If the EVOH layer contains two or more types of EVOH with different ethylene unit contents, the barrier properties of the present film will be reduced. In the present invention, "having a single ethylene unit content" means that the melting peak in differential scanning calorimetry (DSC) is a single peak having only one apex, and two points at half the height (H / 2) of the height (H) from the baseline to the apex of the peak are within ±10°C of the apex temperature. The DSC conditions in the above definition are as follows.

[0019] DSC conditions: Heat from 30°C to 230°C at a rate of 10°C / min, hold at 230°C for 1 minute, then cool to 30°C at a rate of 10°C / min, hold at 30°C for 1 minute, and heat again from 30°C to 230°C at a rate of 10°C / min. The vertical axis of the second heating chart is heat capacity, and the horizontal axis is temperature. The shape of the melting peak is confirmed, and the apex temperature of the melting peak is read. The straight line connecting the point 20°C higher than the apex temperature of the melting peak (point a) and the point 80°C lower than the apex temperature of the melting peak (point b) is taken as the baseline. In addition, two or more kinds of EVOH having different vinyl ester types, physical properties, etc. may be mixed and used as long as they have the same ethylene unit content.

[0020] The degree of saponification of the vinyl ester unit of the EVOH is a value measured based on JIS K6726 (wherein EVOH is a solution uniformly dissolved in a water / methanol solvent), and from the viewpoints of barrier property, thermal stability, and moisture resistance, it is preferably 80 mol% or more, more preferably 90 mol% or more, even more preferably 98 mol% or more, particularly preferably 99 mol% or more, and may be 100 mol%.

[0021] The melt flow rate (MFR) of the EVOH (210°C, load 2.16 kg) is usually 0.5 to 100 g / 10 min, preferably 1 to 50 g / 10 min, and more preferably 3 to 35 g / 10 min. If the MFR is too high, the film formability tends to be unstable, and if it is too low, the viscosity tends to be too high, making melt extrusion difficult.

[0022] The EVOH may be copolymerized with polymerizable monomers other than ethylene and vinyl esters within a range that does not impair the effects of the present invention, generally within a range of 5 mol% or less. Examples of such polymerizable monomers include α-olefins such as propylene, isobutene, α-octene, α-dodecene, and α-octadecene; hydroxyl-containing α-olefins such as 3-butene-1-ol, 4-pentene-1-ol, and 3-butene-1,2-diol, and hydroxyl-containing α-olefin derivatives such as esters and acylates thereof; hydroxymethylvinylidene diacetates such as 1,3-diacetoxy-2-methylenepropane, 1,3-dipropionyloxy-2-methylenepropane, and 1,3-dibutyronyloxy-2-methylenepropane; unsaturated carboxylic acids or salts thereof, partial alkyl esters, complete alkyl esters, nitriles, amides, or anhydrides; unsaturated sulfonic acids or salts thereof; vinylsilane compounds; vinyl chloride; and styrene. These can be used alone or in combination of two or more.

[0023] Furthermore, as the EVOH, EVOH that has been "post-modified" such as urethanized, acetalized, cyanoethylated, or oxyalkylened can also be used.

[0024] The content of EVOH contained in the EVOH layer is not particularly limited, but EVOH is preferably the main component (i.e., the content of EVOH contained in the EVOH layer is 50% by mass or more). The content of EVOH is more preferably 60% by mass or more, further preferably 70% by mass or more, particularly preferably 80% by mass or more, 90% by mass or more, 95% by mass or more, and particularly preferably 100% by mass.

[0025] The EVOH layer may contain components other than EVOH, such as antiblocking agents, processing aids, resins other than EVOH, carboxylic acid compounds, phosphoric acid compounds, boron compounds, metal salts, stabilizers, antioxidants, UV absorbers, plasticizers, antistatic agents, lubricants, colorants, fillers, surfactants, drying agents, crosslinking agents, reinforcing agents such as various fibers, etc., within a range that does not impair the effects of the present invention, generally within a range of 20 mass % or less. These may be used alone or in combination of two or more kinds.

[0026] [Layer containing thermoplastic resin] The base film preferably has a layer containing a thermoplastic resin (hereinafter, sometimes referred to as a "thermoplastic resin layer"). By having the base film have a thermoplastic resin layer, the mechanical strength and barrier property against water vapor of the present film tend to be improved. In addition, properties such as heat sealability and mechanical strength can be imparted depending on the type of thermoplastic resin constituting the thermoplastic resin layer.

[0027] The thermoplastic resin is one other than the EVOH, and examples thereof include polyolefins such as linear low-density polyethylene, low-density polyethylene, very low-density polyethylene, medium-density polyethylene, high-density polyethylene, etc., ethylene-vinyl acetate copolymers, ionomers, ethylene-propylene (block or random) copolymers, ethylene-(meth)acrylic acid copolymers, ethylene-(meth)acrylic acid ester copolymers, polypropylene, propylene-α-olefin copolymers, polybutene, polypentene, etc., or polyolefins graft-modified with unsaturated carboxylic acids or their esters; polyesters; polyamides (including copolymerized polyamides); polyvinyl chloride; polyvinylidene chloride; acrylic resins; polystyrene; polyvinyl esters; polyester elastomers; polyurethane elastomers; chlorinated polystyrene; chlorinated polypropylene; aromatic polyketones or aliphatic polyketones, and polyalcohols obtained by reducing these; polyacetals; polycarbonates, etc. Among these, from the viewpoint of excellent heat sealability and mechanical properties, polyolefins are preferred, polypropylene and polyethylene are more preferred, and polyethylene is particularly preferred. These can be used alone or in combination of two or more.

[0028] When polyethylene is used as the thermoplastic resin, the melt flow rate (MFR) of the polyethylene measured in accordance with JIS K 7210: 2014 (190°C, load 2.16 kg) is preferably 0.10 to 7.5 g / 10 min, more preferably 0.15 to 5.0 g / 10 min, and particularly preferably 0.2 to 2.5 g / 10 min. If the MFR of the polyethylene is within the above range, molding stability tends to be improved.

[0029] The content of the thermoplastic resin in the thermoplastic resin layer is not particularly limited, but it is preferable that the thermoplastic resin is the main component (i.e., the content of the thermoplastic resin contained in the thermoplastic resin layer is 50% by mass or more). The content of the thermoplastic resin is more preferably 60% by mass or more, further preferably 70% by mass or more, particularly preferably 80% by mass or more, 90% by mass or more, 95% by mass or more, and particularly preferably 100% by mass.

[0030] The thermoplastic resin layer may contain components other than the thermoplastic resin, such as antiblocking agents, processing aids, resins other than thermoplastic resins, carboxylic acid compounds, phosphoric acid compounds, boron compounds, metal salts, stabilizers, antioxidants, UV absorbers, plasticizers, antistatic agents, lubricants, colorants, fillers, surfactants, drying agents, crosslinking agents, reinforcing agents such as various fibers, etc., within a range that does not impair the effects of the present invention, generally within a range of 20 mass % or less. These may be used alone or in combination of two or more kinds.

[0031] [Layer containing adhesive resin] The base film may have a layer containing an adhesive resin (hereinafter, may be referred to as an "adhesive resin layer"). When the base film has an adhesive resin layer, the appearance characteristics (film surface) of the present film tend to be better.

[0032] The adhesive resin is not particularly limited, but is preferably a polyolefin having a carboxy group, a carboxylic anhydride group, or an epoxy group, and more preferably a polyolefin having a carboxylic anhydride group. Such adhesive resins tend to have excellent adhesion to the EVOH layer and / or the thermoplastic resin layer.

[0033] Examples of polyolefins containing carboxyl groups include polyolefins copolymerized with acrylic acid or methacrylic acid. In this case, all or part of the carboxyl groups contained in the polyolefin may be present in the form of a metal salt, as typified by ionomers. Examples of polyolefins having carboxylic anhydride groups include polyolefins graft-modified with maleic anhydride or itaconic acid. Examples of polyolefins having epoxy groups include polyolefins copolymerized with glycidyl methacrylate. Among these, polyolefins having carboxylic anhydride groups such as maleic anhydride, and particularly polyethylene having carboxylic anhydride groups, can be used. These can be used alone or in combination of two or more kinds.

[0034] The melt flow rate (MFR) of the adhesive resin measured according to JIS K 7210:2014 (190°C, load 2.16 kg) is not particularly limited, but is preferably 0.1 to 20.0 g / 10 min, more preferably 1.0 to 10.0 g / 10 min. When the MFR of the adhesive resin is within the above range, molding stability tends to be improved.

[0035] The content of the adhesive resin in the adhesive resin layer is not particularly limited, but the adhesive resin is preferably the main component (i.e., the content of the adhesive resin contained in the adhesive resin layer is 50% by mass or more). The content of the adhesive resin is more preferably 60% by mass or more, even more preferably 70% by mass or more, particularly preferably 80% by mass or more, 90% by mass or more, 95% by mass or more, and 100% by mass is particularly preferred.

[0036] The adhesive resin layer may contain components other than the adhesive resin, such as antiblocking agents, processing aids, resins other than the adhesive resin, carboxylic acid compounds, phosphoric acid compounds, boron compounds, metal salts, stabilizers, antioxidants, UV absorbers, plasticizers, antistatic agents, lubricants, colorants, fillers, surfactants, drying agents, crosslinking agents, reinforcing agents such as various fibers, etc., within a range that does not impair the effects of the present invention, generally within a range of 20 mass % or less. These may be used alone or in combination of two or more kinds.

[0037] [Method of manufacturing base film] The substrate film can usually be produced by extruding the raw material for forming the EVOH layer through a die, forming it into a film, and uniaxially stretching it. In addition, when the base film has a thermoplastic resin layer or an adhesive resin layer, the base film can be produced by forming each raw material composition forming the EVOH layer, the thermoplastic resin layer, and the adhesive resin layer into a film by conventional coextrusion in which the raw material compositions are extruded from separate dies or a common die and laminated, and then uniaxially stretching the film. As the die, for example, a circular die or a T-die can be used. Examples of the molding method include extrusion molding, blow molding, injection molding, thermoforming, cast molding, and inflation molding.

[0038] The base film is not particularly limited as long as it has an EVOH layer. Since the base film has an EVOH layer, the present film having excellent transparency can be obtained. The base film is preferably multilayered. When the EVOH layer is the "(A) layer", the thermoplastic resin layer is the "(B) layer", and the adhesive resin layer is the "(C) layer", examples of the layer configuration include layer (B) / layer (A), layer (B) / layer (A) / layer (B), layer (B) / layer (C) / layer (A) / layer (B), layer (B) / layer (C) / layer (A) / layer (C) / layer (B), layer (B) / layer (A) / layer (B) / layer (A) / layer (B), layer (B) / layer (B) / layer (B) / layer (A) / layer (B), layer (B) / layer (B) / layer (B) / layer (C) / layer (A) / layer (C) / layer (B), layer (B) / layer (A) / layer (B) / layer (B), layer (B) / layer (B) / layer (C) / layer (A) / layer (C) / layer (B) / layer (B), and the like. In the above examples, layers (B) and (C) are exemplified as layers other than layer (A), but layers other than layer (A) are not limited to these. Moreover, it is preferable that the base film does not include a layer formed from a resin composition containing a polyamide-based resin as a main component (that is, a resin composition containing 50% by mass or more of a polyamide-based resin). In the above examples, the " / " sign means that the layers on both sides of the " / " sign are directly laminated.

[0039] The substrate film thus obtained is a uniaxially stretched film. The stretching ratio of the uniaxially stretched film is preferably at least 3, more preferably at least 4, and particularly preferably at least 5. If the stretching ratio is less than 3, thickness unevenness due to stretching tends to occur and gas barrier properties tend to deteriorate. The upper limit of the stretching ratio is preferably not more than 12, more preferably not more than 10, and particularly preferably not more than 8. If the stretching ratio exceeds 12, the film surface after stretching tends to deteriorate. The use of a uniaxially stretched film has the advantages of being economical, making the multilayer structure easier to tear (making it easier to open the packaging material when used as such), and improving the gas barrier properties.

[0040] The stretching direction of the uniaxially stretched film is not particularly limited and may be either the longitudinal direction (MD direction) or the transverse direction (TD direction). However, uniaxial stretching in the longitudinal direction (MD direction) is preferred, and it is particularly preferred that the film is not substantially stretched in a direction different from the stretching direction. The stretched state of the substrate film (unstretched, uniaxially stretched, biaxially stretched, etc.) can be confirmed by using a general method for analyzing the orientation of a resin (e.g., wide-angle X-ray scattering (WAXS), etc.).

[0041] The stretching method of the uniaxially stretched film is not particularly limited, but examples thereof include tenter stretching, tubular stretching, roll stretching, etc. Among them, from the viewpoint of production cost, uniaxial stretching by roll stretching is preferred. In addition, when the base film is obtained by inflation molding, roll stretching is preferred.

[0042] The stretching temperature during uniaxial stretching is not particularly limited, but is generally 50 to 130°C.

[0043] The total thickness of the base film is not particularly limited and can be appropriately set according to the application. The thickness of the base film is preferably 10 μm or more, more preferably 15 μm or more. When the thickness of the base film is 10 μm or more, industrial productivity and mechanical properties tend to be improved. In addition, the thickness of the base film is preferably 100 μm or less, more preferably 50 μm or less. When the thickness of the base film is 100 μm or less, industrial productivity and economic efficiency tend to be improved. The thickness of the substrate film, which is a uniaxially stretched film, means the thickness after stretching.

[0044] When the base film is a multi-layer film, the thickness of the EVOH layer is preferably 0.5 μm or more, more preferably 0.8 μm or more, and particularly preferably 1 μm or more. When the thickness of the EVOH layer is 0.5 μm or more, the gas barrier property tends to be improved. On the other hand, the thickness of the EVOH layer is preferably 20 μm or less, more preferably 10 μm or less, and particularly preferably 5 μm or less. When the thickness of the EVOH layer is 20 μm or less, the appearance characteristics (film surface) tend to be good. The thickness of the multi-layer film, which is a uniaxially stretched film, means the thickness after stretching. When the EVOH layer is provided in multiple layers on the base film, the total thickness of all the EVOH layers is preferably within the above range.

[0045] When the base film is a multilayer film, the ratio of the thickness of the EVOH layer to the total thickness of all layers is preferably 30% or less, more preferably 20% or less, and may be 10% or less, or 5% or less, from the viewpoints of industrial productivity and mechanical properties.

[0046] When the base film has a thermoplastic resin layer, the thickness thereof is preferably from 7 to 100 μm, more preferably from 10 to 50 μm, from the viewpoints of industrial productivity and mechanical properties. In the case of a substrate film which is a uniaxially stretched film, the thickness of the thermoplastic resin layer means the thickness after stretching. In addition, when the substrate film has multiple thermoplastic resin layers, it is preferable that the total thickness of all the thermoplastic resin layers is in the above range.

[0047] When the base film has an adhesive resin layer, the thickness thereof is preferably from 0.5 to 20 μm, more preferably from 1 to 10 μm, from the viewpoints of industrial productivity and quality stability. In the case of a substrate film that is a uniaxially stretched film, the thickness of the adhesive resin layer means the thickness after stretching. In addition, when the adhesive resin layer is provided in a multi-layer structure on the substrate film, it is preferable that the total thickness of all the adhesive resin layers is in the above range.

[0048] The internal haze value of the substrate film is preferably less than 0.4%, more preferably 0.3% or less, particularly preferably 0.2% or less, 0%. The internal haze value can be measured using a substrate film having a thickness of 33 μm and a haze meter in accordance with ASTM D1003.

[0049] <Metal deposition layer> The metal deposition layer laminated on the base film is obtained by depositing a single metal or an alloy. The metal deposition layer does not contain metal compounds such as metal oxides and metal nitrides. Examples of metals used in the metal deposition layer include those classified as aluminum group elements (aluminum, gallium, indium, etc.), tin group elements (titanium, zirconium, tin, hafnium, etc.), precious metals (copper, silver, gold, etc.), chromium group elements (chromium, molybdenum, tungsten, etc.), and iron group elements (iron, cobalt, nickel, etc.), and alloys thereof. In particular, the metal deposition layer is preferably made of at least one selected from the group consisting of aluminum, gold, silver, copper, titanium, nickel, chromium, tin, and indium, and is particularly preferably made of aluminum, in terms of general availability and ease of handling. From the viewpoint of barrier properties, it is preferable that the metal vapor deposition layer is laminated on the EVOH layer of the base film.

[0050] <Manufacturing method of this film> The present film can be produced by laminating the above-mentioned metal vapor deposition layer on the above-mentioned base film.

[0051] The method for laminating the metal vapor deposition layer on the base film is not particularly limited, and any known vapor deposition method may be appropriately adopted, for example, a physical vapor deposition method (PVD method) such as a vacuum deposition method, a sputtering method, or an ion plating method, or a chemical vapor deposition method (CVD method).

[0052] The thickness of the metal vapor deposition layer is usually 1 to 100 nm, preferably 3 to 50 nm, and more preferably 5 to 20 nm. If the thickness of the metal vapor deposition layer is less than 1 nm, the barrier property tends to be insufficient, while if the thickness exceeds 100 nm, the barrier property is not improved and the bending resistance and production costs tend to increase.

[0053] The oxygen permeability of the film thus obtained at 20°C and 90% RH is 8cc / m 2 ·day·atm or less is preferable, and 7cc / m 2 ·day·atm or less is preferable, 5cc / m 2 ·day·atm or less is particularly preferable.

[0054] The present film can be suitably used as a molding for packaging general foods, as well as seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, snacks, beverages, cosmetics, medicines, etc., as well as packaging materials such as packaging films, or as part of multilayer structures for forming these.

[0055] <<Multilayer structure>> The multilayer structure is obtained by laminating another layer on the present film. The other layer to be laminated on the present film is not particularly limited, and may be a layer formed from a resin composition containing the thermoplastic resin exemplified above as the thermoplastic resin or the adhesive resin exemplified above as the adhesive resin.

[0056] As a method for producing the multilayer structure, various known production methods such as a dry lamination method, a sand lamination method, an extrusion lamination method, a coextrusion lamination method, a solution coating method, etc. can be used.

[0057] <<Molded body>> The film or the multilayer structure can be used to obtain a molded product in the shape of a cup or tray. In this case, a drawing method is usually used, specifically, a vacuum forming method, a pressure forming method, a vacuum pressure forming method, a plug-assisted vacuum pressure forming method, etc. Furthermore, it is also possible to obtain a molded body such as a tube or bottle-shaped multilayer container (laminate structure) from a multilayer parison (a hollow tubular preform before blowing) using the multilayer structure. In this case, a blow molding method is usually used, and specific examples thereof include an extrusion blow molding method (double-head type, mold moving type, parison shift type, rotary type, accumulator type, horizontal parison type, etc.), a cold parison type blow molding method, an injection blow molding method, and a biaxial stretch blow molding method (extrusion type cold parison biaxial stretch blow molding method, injection type cold parison biaxial stretch blow molding method, injection molding in-line type biaxial stretch blow molding method, etc.). The resulting laminate may be subjected to processes such as heat treatment, cooling, rolling, printing, dry lamination, solution or melt coating, bag making, deep drawing, box processing, tube processing, and splitting, as required. EXAMPLES

[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are based on mass. Prior to the examples, the following materials were prepared.

[0059] <evoh> EVOH1: Ethylene unit content 29 mol%, MFR (210°C, load 2.16 kg): 3.8 g / 10 min, saponification degree 99.9 mol% EVOH2: Ethylene unit content 32 mol%, MFR (210°C, load 2.16 kg): 3.8 g / 10 min, saponification degree 99.9 mol% EVOH3: Ethylene unit content 25 mol%, MFR (210°C, load 2.16 kg): 4.0 g / 10 min, saponification degree 99.9 mol% EVOH4: Ethylene unit content 44 mol%, MFR (210°C, load 2.16 kg): 3.5 g / 10 min, saponification degree 99.9 mol%

[0060] <Thermoplastic resin> Polyethylene: Novatec HY540 manufactured by Mitsubishi Chemical Corporation, MFR (190℃, load 2.16kg): 1.0g / 10min

[0061] <Adhesive resin> Acid-modified polyethylene resin: Mitsubishi Chemical Corporation's "Modic M545", MFR (190°C, load 2.16 kg): 6.0 g / 10 min

[0062] [Example 1] ● Manufacturing of base film EVOH1, polyethylene, and acid-modified polyethylene resin were fed into a multilayer cast film device (manufactured by Plastics Engineering Research Institute) and co-extruded under the following multilayer co-extrusion molding conditions to obtain a multilayer film with a three-layer structure of EVOH layer / adhesive resin layer / thermoplastic resin layer. The thicknesses (μm) of each layer of the obtained multilayer film were 20 / 10 / 170. (Multi-layer co-extrusion molding conditions) EVOH layer: 40mmφ single screw extruder (barrel temperature: 210℃) Thermoplastic resin layer: 40mmφ single screw extruder (barrel temperature: 230℃) Adhesive resin layer: 32mmφ single screw extruder (barrel temperature: 200℃) Die: 4-type 5-layer feed block type T die (die temperature: 230℃) Take-off speed: 5m / min

[0063] The obtained multilayer film was stretched 6 times in the longitudinal direction (MD direction) using a stretching device (manufactured by MEC Techno Co., Ltd.) by passing it between a roll whose surface temperature (stretching temperature) was heated to 120°C and another roll rotating at a different speed, to obtain a substrate film (uniaxially stretched film). The thicknesses (μm) of the layers in the obtained substrate film were 3.3 / 1.7 / 28.3.

[0064] -Layering of metal deposition layers Using a batch-type deposition facility manufactured by Showa Shinku, a metal deposition layer of aluminum was laminated on the EVOH layer surface of the base film while the film surface temperature was kept at 40° C. or lower, to obtain the deposition film of Example 1.

[0065] [Comparative Example 1] A vapor-deposited film of Comparative Example 1 was obtained in the same manner as in Example 1, except that EVOH1 used in Example 1 was changed to EVOH2.

[0066] [Comparative Example 2] A vapor-deposited film of Comparative Example 2 was obtained in the same manner as in Example 1, except that the EVOH1 used in Example 1 was changed to a mixture of EVOH3 and EVOH4 in a mass ratio of 75:25.

[0067] [Comparative Example 3] The deposition film of Comparative Example 3 was obtained in the same manner as in Example 1, except that the multilayer film obtained in Example 1 was stretched 2 times in the MD direction and 3 times in the TD direction (stretched 6 times in total) using a tenter-type biaxial stretching machine (manufactured by Brukner). That is, in Comparative Example 3, a biaxially stretched film is used as the base film. The thicknesses (μm) of the layers in the obtained substrate film were 3.3 / 1.7 / 28.3.

[0068] [Reference example 1] The multilayer film obtained in Example 1 was not laminated with a metal vapor deposition layer. That is, Reference Example 1 is a uniaxially stretched film itself that does not have a metal vapor deposition layer.

[0069] The thus obtained vapor-deposited films of Example 1 and Comparative Examples 1 to 3, and the multilayer film of Reference Example 1 were used to measure and evaluate "barrier properties" and "interaction with metals" as described below. The measurement and evaluation results are shown in Table 1 below.

[0070] <Barrier properties> Using an oxygen permeability measuring device (Ox-tran2 / 21, Hitachi High-Tech), oxygen permeability (cc / m 2 ·day·atm) was measured. 2 A larger value of 0.1·day·atm indicates higher oxygen permeability and poorer barrier properties. The measured oxygen permeability was evaluated according to the following indices. 〇(Good): 0.05(cc / m 2 ·day·atm) △(possible):0.05(cc / m 2 ·day · atm) or more 0.12 (cc / m) 2 ·day·atm) ×(bad): 0.12(cc / m 2 ·day · atm) or more

[0071] <Interaction with metals> Using a thermogravimetric analyzer (Perkin Elmer, Pyris 1 TGA), the temperature (℃) at which the polymer weight becomes 0 was measured under the conditions of a nitrogen atmosphere, air flow rate: 20 mL / min, heating rate: 10℃ / min, and temperature range: 30 to 550℃. The polymer weight is the total weight (polymer amount + metal deposition amount) minus the final remaining amount (metal deposition amount). The higher this temperature, the stronger the interaction with the metal (the better the heat resistance). The measured temperature (℃) was evaluated according to the following index. Good: 525℃ or higher △(OK): 520℃ or higher and less than 525℃ × (bad): below 520℃

[0072] [Table 1]

[0073] The results shown in Table 1 show that the vapor-deposited film of Example 1, which comprises a uniaxially stretched substrate film containing EVOH having a single ethylene unit content and an ethylene content of less than 32 mol%, and a metal vapor-deposited layer, has excellent barrier properties and strong interaction with metals. On the other hand, the deposited film of Comparative Example 1, which used EVOH with an ethylene content of 32 mol%, the deposited film of Comparative Example 2, which used two types of EVOH, and the deposited film of Comparative Example 3, which used a biaxially stretched substrate film, were inferior to the deposited film of Example 1 in both barrier properties and interaction with metals. [Industrial Applicability]

[0074] The present film can be suitably used as a molding for packaging general foods, as well as seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, snacks, beverages, cosmetics, medicines, etc., as well as packaging materials such as packaging films, or as part of multilayer structures for forming these.< / evoh>

Claims

1. A vapor-deposited film comprising a base film having a layer containing an ethylene-vinyl alcohol-based copolymer and a metal vapor-deposited layer laminated on the base film, The substrate film is a uniaxially stretched film, The ethylene-vinyl alcohol copolymer has a single ethylene unit content and an ethylene content of less than 32 mol %.

2. 2. The vapor-deposited film according to claim 1, wherein the substrate film is a uniaxially stretched film having a stretch ratio of 3 or more.

3. 3. The vapor-deposited film according to claim 1, wherein the substrate film is a multi-layer film further comprising a layer containing a thermoplastic resin.

4. 3. The vapor-deposited film according to claim 1, wherein the vapor-deposited metal layer comprises at least one selected from the group consisting of aluminum, gold, silver, copper, titanium, nickel, chromium, tin, and indium.

5. A multilayer structure comprising the vapor-deposited film according to claim 1 or 2.

6. A molded article comprising the vapor-deposited film according to claim 1 or 2.

Citation Information

Patent Citations

  • Resin film for surface treatment and multilayered film using it

    JP2005290108A

  • Vapor deposition film, packaging material and vacuum heat insulation body

    JP2016028886A

  • Multilayer film having excellent recoverability

    WO2021210606A1